Pharmaceutical Preparation of Prabhkara Vati - An Ayurvedic Formulation - Anju M; Anand S (International Journal of Ayurveda and Pharma Research, 2025)
Prabhakara Vati, an Ayurvedic formulation, plays a significant role in treating heart-related ailments, as emphasized in the Bhaishajya Ratnavali (Hridroga Prakarana) and the Ayurvedic Formulary of India (Part 1). The preparation involves five key ingredients: Sudha Abraka Bhasma, Sudha Loha Bhasma, Sudha Swarna Makshika Bhasma, Sudha Shilajathu, and Tugaksheeri (Bamboo Manna). The preparation involves using Terminalia arjuna bark decoction during trituration (Bhavana), which enhances its medicinal properties and supports its cardioprotective function. The preparation of Prabhakara vati involves preprocessing of Abraka Bhasma, Loha Bhasma, Swarna Makshika Bhasma, and Shilajit Sodhana, each performed according to classical Ayurvedic methods. Each Bhasma was prepared by purification (Sodhana) process followed by incineration (Marana). Purification of Abraka, Loha, and Swarnamakshika was carried out by Nirvapa (quenching) method while Shilajthu sodhana by Suryatapi method mentioned in Rasataragini. After purification, incineration was done for each ingredient based on classical reference: 5 Puta (incineration) for Abraka bhasma, 8 Puta for Loha basma, and 6 Puta for Swarna makshika. Subsequently, Bhasma pareeksha was carried out to test the quality of each Bhasma. After the preprocessing of this Bhasma, Prabhakara vati was prepared by triturating an equal amount of each five ingredients with Arjuna kashaya, which was prepared using Bhavana method. Special care is taken to maintain the purity and authenticity of ingredients, ensuring the formulation retains its therapeutic efficacy. This work is a comprehensive documentation of the step-by-step preparation of Prabhakara Vati, conducted at Government Ayurveda College in Thiruvananthapuram, and provides a detailed guideline for the formulation process described herein.